Unraveling Consumer Mindset: Analysis of Consumer Behavior in the Distribution of E-WOM on The Originote Skincare Product - Nurul Qurrotul Aini; Fadhilah Nur Oktaviani; Sudarmiatin Sudarmiatin (Lafadz Jaya Publisher, 2025)
This study aims to analyze the spread of e-WOM on the skincare brand